2013
DOI: 10.1002/qua.24575
|View full text |Cite
|
Sign up to set email alerts
|

Ro-vibrational studies of diatomic molecules in a shifted Deng-Fan oscillator potential

Abstract: Bound-state spectra of shifted Deng-Fan oscillator potential are studied by means of a generalized pseudospectral method. Very accurate results are obtained for both low as well as high states by a non-uniform optimal discretization of the radial Schrödinger equation. Excellent agreement with literature data is observed in both s-wave and rotational states. Detailed variation of energies with respect to potential parameters is discussed. Application is made to the ro-vibrational levels of four representative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Our currently found energy states are reasonably compared with the other findings. The vibrational energy is close to 7 digits with AIM [27] but found to agree with GPS [26] up to 4 digits. However, the rotational-vibrational energy states are close close to 5 digits with AIM.…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
“…Our currently found energy states are reasonably compared with the other findings. The vibrational energy is close to 7 digits with AIM [27] but found to agree with GPS [26] up to 4 digits. However, the rotational-vibrational energy states are close close to 5 digits with AIM.…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
“…Its importance in the field of molecular science is well‐known. DF potential qualitatively represents the Morse potential and shows the correct asymptotic behavior as internuclear distance tends toward zero and infinity . Hence, DF potential has many applications in molecular spectroscopy.…”
Section: Introductionmentioning
confidence: 80%
“…Hence, DF potential has many applications in molecular spectroscopy. In this work, a modified DF potential, with an infinite potential wall placed at r 0 has been assumed. The resulting Schrödinger equation has been solved using accurate five‐point finite difference method.…”
Section: Introductionmentioning
confidence: 99%
“…Just of recent, a modified form of Deng-Fan potential called the shifted Deng-Fan potential was suggested by Hamzavi et al (2013), it was reported that the shifted Deng Mustafa (2015) to investigate a new deformed Schioberg-type potential, and obtained ro-vibrational energies for some diatomic molecule [13]. He showed how this potential is related to the Deng-Fan potential [14].…”
Section: Introductionmentioning
confidence: 99%